Criminal justice in Scotland - Buchan, Jamie (Routledge, 2026)
"Providing a comprehensive and up-to-date introduction to the contemporary Scottish criminal justice system, this book focuses on its key processes (from arrest to post-sentence) and institutions, as well as its history and some of the key challenges and critical issues facing Scottish criminal justice today. Highly attentive to procedural and institutional detail, the book is underpinned by a critical sociological perspective. The opening chapter considers Scotland in its post-devolutionary context within the UK, setting the scene for Scottish criminal justice institutions. Subsequent chapters deal in turn with different institutions and processes of Scottish criminal justice: surveillance and crime prevention, policing, prosecution and the courts, criminal fines and other financial penalties, community justice, electronic monitoring, prisons, youth justice, and parole and post-sentence reintegration and supervision. The final chapter draws on comparative and international criminology to look at Scottish criminal justice in changing international contexts and its response to new global crimes. Designed to support learning, it includes Key ideas at the start of each chapter, outlining expectations, and providing a very high-level summary of the most important points. Text boxes covering key issues, controversies and/or key populations in focus. Case studies of specific problems and events in Scottish criminal justice. Critical questions to challenge students to develop their own thinking and ideas about key issues in Scottish criminal justice. Short, informal interviews with key practitioners and researchers. Essential Readings and Key Resources at the end of each chapter. Criminal Justice in Scotland will be a key text for students of criminology and criminal justice, particularly those with an interest in the Scottish criminal justice system. It will also be of value to students of law, social work and social policy"-- Provided by publisher